Assessment of Using Field‐Aligned Currents to Drive the Global Ionosphere Thermosphere Model: A Case Study for the 2013 St Patrick’s Day Geomagnetic Storm - Qingyu Zhu; Gang Lu; Astrid Maute; Yue Deng; Brian Anderson (Space Weather)
Abstract In this study, field‐aligned currents (FACs) obtained from the Active Magnetosphere and Planetary Electrodynamics Response Experiment data set have been used to specify the high‐latitude electric potential in the Global Ionosphere Thermosphere Model (GITM). The advantages and challenges of the FAC‐driven simulation are investigated based on a series of numerical experiments and data‐model comparisons for the 2013 St Patrick's Day geomagnetic storm. It is found that the cross‐track ion drift measured by the Defense Meteorological Satellite Program satellites can be well reproduced in the FAC‐driven simulation when the electron precipitation pattern obtained from Assimilative Mapping of Ionospheric Electrodynamics (AMIE) technique is used in GITM. It is also found that including the neutral wind dynamo properly is very important when using FACs to derive the high‐latitude electric field. Without the neutral wind dynamo, the cross‐polar‐cap potential and hemispheric integrated Joule heating could be underestimated by more than 20%. Moreover, the FAC‐driven simulation is able to well reproduce the ionospheric response to the geomagnetic storm in the American sector. However, the FAC‐driven simulation yields relatively larger data‐model discrepancies compared to the AMIE‐driven GITM simulation. This may result from inaccurate Joule heating estimations in the FAC‐driven simulation caused by the inconsistency between the FAC and electron precipitation patterns. This study indicates that the FAC‐driven technique could be a useful tool for studying the coupled ionosphere and thermosphere system provided that the FACs and electron precipitation patterns can be accurately specified.